Examining student responses of PhET simulations after virtual laboratory practices - Nurul Azzubairiyah; Erman Erman; Enny Susiyawati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aims to describe students' responses to implementing PhET Simulations after joining a virtual laboratory practice. This study employed a survey method. The samples of this study included 80 students in eighth grade, and the data collection was conducted using the questionnaire of students' responses to the use of PhET Simulation. The data of students' responses were displayed in percentages and grouped into five categories: very good, good, satisfying, sufficient, and insufficient. The study results showed that students' interest in PhET Simulations was categorized as good. Group learning feasibility using PhET Simulations was categorized as satisfying, the novelty of PhET Simulations for students was categorized as good, the effectiveness of PhET Simulations was categorized as good, and new information gained from PhET Simulations was categorized as good. The average of students' responses was categorized as good. The results revealed that students respond well to the implementation of PhET Simulations in virtual laboratory practice activities, which should be implemented in the science learning activity during Covid-19 pandemics.